Examining the Impacts of Wife Abuse and Child Abuse on Saudi Women’s Mental and Physical health - Alhalal, Eman (2016)
Research has not extensively examined the contextual mechanisms by which Intimate Partner Violence (IPV) and child abuse lead to chronic pain. Post-traumatic Stress Disorder (PTSD) and depressive symptoms overlap, yet, it is not clear whether they function in unique ways as mediators of the relationships of abuse with chronic pain. Thus, the purposes of this study were to: a) test a causal model that explains the mechanisms by which severity of child abuse and wife abuse affect chronic pain among Saudi women, and the mediating role of symptoms of depression and PTSD and perceived family support and, b) advance the measurement of IPV and health problems associated with it by evaluating the psychometric properties of Arabic versions of the Composite Abuse Scale (CAS) and PTSD Checklist—Civilian Version (PCL-C). A two-phase study design was used. In Phase one, a pilot study was conducted to translate three self-report measures from English to Arabic and to assess their reliability in a sample of 30 Arab women. In Phase two, the theoretical model was tested using data from 299 Saudi women. The psychometric properties of Arabic versions of both PCL-C and CAS were examined. Structural equation modeling was used to test the hypothesized model two times using different mental health outcomes. Initial support for the reliability and concurrent and construct validity of the PCL-C and CAS were found. Both theoretical models were found to fit the data. In both models, severity of wife abuse and child abuse did not affect chronic pain directly, but indirectly, through mental health, although the strength of the path coefficients differed. Severity of wife and child abuse were directly associated with greater mental health IV problems and less perceived family support. Family support partially mediated the relationship between abuse and depressive symptoms but not PTSD symptoms. The results demonstrate the reliability and validity of the Arabic versions of the PCL-C and Arabic CAS. The study substantially contributes to the literature by delineating the mediating role of PTSD and depressive symptoms. The findings underscore the significance of considering abuse experiences and mental health in chronic pain treatment